GPETAFLR: A new anti-inflammatory peptide from Lupinus angustifolius L. protein hydrolysate. (October 2015) - Millán-Linares, Mª del Carmen; Millán, Francisco; Pedroche, Justo; Yust, María del Mar
Highlights: A potential anti-inflammatory peptide was purified from lupine protein hydrolysate. The sequence was Gly-Pro-Glu-Thr-Ala-Phe-Leu-Arg. This octapeptide may help to prevent diseases related to chronic inflammation. Abstract: An anti-inflammatory peptide was identified in lupine protein hydrolysate (LPH) obtained by enzymatic hydrolysis of lupine protein isolate (LPI) with Alcalase. LPH was separated in two fractions by ultrafiltration, and anti-inflammatory activity was evaluated by analysis of the expression of different cytokines in THP-1-derived macrophages by quantitative PCR (qPCR). Fraction <10 kDa was purified by chromatographic techniques, and the most active subfraction was analysed by mass spectrometry. A novel anti-inflammatory peptide was identified and the sequence was Gly-Pro-Glu-Thr-Ala-Phe-Leu-Arg. This peptide was synthesised, and its anti-inflammatory activity was tested at two concentrations. Expression of TNF, IL-1β, and CCL2 was significantly reduced whereas the expression of the anti-inflammatory cytokine IL-10 was induced. Regarding the production of cytokines, only the lowest concentration of the synthetic peptide showed anti-inflammatory properties. Furthermore, the synthetic peptide decreased nitric oxide production. Thus, the identified peptide may help to prevent chronic inflammation associated with several diseases.